Tagetes erecta ‘Perfection Yellow’ ‘Perfection Yellow’ Marigold - Edward Gilman (EDIS, 2007)
This document provides an overview of Tagetes erecta ‘Perfection Yellow’, commonly known as ‘Perfection Yellow’ marigold. It describes the plant’s characteristics, including its height, spread, and flower colors, which range from yellow to bicolored. The document also covers the plant’s growth requirements, such as full sun and well-drained soil, and its susceptibility to pests and diseases. Additionally, it highlights the plant’s uses in landscaping, including as a border plant and in containers, and offers tips for maintaining its appearance and health. Original publication date October 1999.